2000
DOI: 10.1302/0301-620x.82b8.0821117
|View full text |Cite
|
Sign up to set email alerts
|

Use of hydroxyapatite to fill cavities after excision of benign bone tumours

Abstract: Much of the basic research on calcium hydroxyapatite (HA) has concerned its clinical use as a bone-graft substitute. Biological, 1,2 histological 3-12 and biomechanical surveys of its implantation into bone [13][14][15] reveal that the material is safe and has excellent osteoconductive properties. It is often used as a coating for prostheses as well as to fill bone defects. [16][17][18] There have, however, been few reports on the outcome of its clinical use in surgery for bone tumours. 19,20 Since 1988, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 29 publications
2
25
0
4
Order By: Relevance
“…According to the macroscopic results of this research, it was not found signs of rejection of hydroxyapatite, confirming the biocompatibility of this substance (Oonishi et al, 1997;Schmitz et al, 1999;Shirane et al;Yamamoto et al, 2000).…”
Section: Discussionsupporting
confidence: 72%
“…According to the macroscopic results of this research, it was not found signs of rejection of hydroxyapatite, confirming the biocompatibility of this substance (Oonishi et al, 1997;Schmitz et al, 1999;Shirane et al;Yamamoto et al, 2000).…”
Section: Discussionsupporting
confidence: 72%
“…As HA exhibits a high affinity to bone with a moderate strength, it is commonly used as a filler to replace bone defects subsequent to tumor resection or as a coating to promote bone ingrowth into prosthetic implants. PMMA bone cement is also clinically used in orthopedic surgery as a bone graft substitute (18,19), for implant arthroplasty, and to strengthen bone. These materials may also be applied in orthopedic surgery as sustained-release systems for certain drugs, including antibiotics and antitumor agents (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Assim como o descrito por Yamamoto et al (2000) e Vital et al (2006), as radiografias obtidas imediatamente após o procedimento cirúrgico mostraram que o compósito foi bem colocado no osso receptor (Fig. 3A).…”
Section: Resultsunclassified